1997
DOI: 10.1038/nbt0297-155
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of antiidiotypic single chain antibodies with yeast killer toxin activity

Abstract: Single chain fragment (ScFv) antiidiotypic antibodies (antilds) of a killer toxin (KT) from the yeast Pichia anomala have been produced by recombinant DNA methodology from the splenic lymphocytes of mice immunized by idiotypic vaccination with a KT-neutralizing monoclonal antibody (Mab KT4). ScFv KT-like antilds (KTIdAb) react with specific Candida albicans KT cell wall receptors (KTR) exerting a candidacidal activity in vitro could be neutralized by adsorption with Mab KT4. ScFv KTIdAb displayed an effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 22 publications
2
114
0
Order By: Relevance
“…On closer examination, however, in at least one case, T H 2-derived antibodies have a protective effect by somehow augmenting cell-mediated immunity 39 . In other cases, antibodies can function as opsonins, promoting fungal ingestion and even killing by phagocytes, and several antibodies are directly fungicidal [40][41][42][43][44][45][46][47] (TABLE 1). These kinds of activities are complementary, rather than exclusive, to cell-mediated mechanisms.…”
Section: Evidence For Protective Antibodies Against Fungal Diseasementioning
confidence: 99%
“…On closer examination, however, in at least one case, T H 2-derived antibodies have a protective effect by somehow augmenting cell-mediated immunity 39 . In other cases, antibodies can function as opsonins, promoting fungal ingestion and even killing by phagocytes, and several antibodies are directly fungicidal [40][41][42][43][44][45][46][47] (TABLE 1). These kinds of activities are complementary, rather than exclusive, to cell-mediated mechanisms.…”
Section: Evidence For Protective Antibodies Against Fungal Diseasementioning
confidence: 99%
“…The Totiviridae family is composed by four genera whose members have non-segmented dsRNA genomes, encapsidated in isometric virions called Virus-Like Particles (VLPs), which have no lipids or carbohydrates [1,2]. The virus L-A (ScV-L-A) of Saccharomyces cerevisiae is the type species of genus Totivirus and is one of the most studied mycovirus.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, based on this report, it might be concluded that younger patients probably benefit from IVIg therapy. Also modifications in the immune system due to previous drugs/therapies in adult patients might influence the [148]. A decapeptide resulting from the variable region sequence and containing part of the CDR1 segment of the KT-scFv light chain also exerted therapeutic activity against experimental mucosal and systemic candidiasis [149].…”
Section: Role Of Antibodies In the Protection Against Fungal Infectiomentioning
confidence: 99%